Ontogenesis of the Gut Microbiota Composition in Healthy, Full-Term, Vaginally Born and Breast-Fed Infants over the First 3 Years of Life: A Quantitative Bird’s-Eye View - Nagpal, Ravinder; Tsuji, Hirokazu; Takahashi, Takuya; Nomoto, Koji; Kawashima, Kazunari; Nagata, Satoru; Yamashiro, Yuichiro (Frontiers in Microbiology, 2017)
Early-life intestinal microbiota development is crucial for host’s long-term health and is influenced by many factors including gestational age, birth and feeding modes, birth environment, ethnic/ geographical background etc. However, ‘quantitative’ data on the actual population levels of gut bacterial communities when these influences are controlled for is relatively rare. Herein, we demonstrate a quantitative perspective of microbiota development in natural and healthy milieus i.e. in healthy, full-term, vaginally-born and breast-fed infants (n=19) born at same clinic. Fecal microbiota at age 1 and 7 days, 1, 3 and 6 months and 3 years is quantified using highly sensitive reverse-transcription-quantitative-PCR assays targeting bacterial rRNA molecules. At day 1, we detect one or more bacteria in all (100%) of the babies, wherein the microbiota is composed mainly of enterobacteria (35%), Bacteroides fragilis group (23%), enterococci (18%), staphylococci (13%) and bifidobacteria (9%). Altogether, facultative anaerobes predominate during first few weeks whereafter obligate anaerobes including bifidobacteria, B. fragilis group, Clostridium coccoides group and Clostridium leptum subgroup gradually start prevailing. At 3 years, the composition is represented almost entirely (99%) by obligate anaerobes including C. leptum subgroup (34%), bifidobacteria (22%), B. fragilis group (21%), C. coccoides group (17%), Atopobium cluster (4%) and Prevotella (1%). The overall obligate/facultative proportion is 32/68, 37/63, 54/46, 70/30, 64/36 and 99/1% at 1 and 7 days, 1, 3 and 6 months and 3 years, respectively. However, interestingly, considerable individual-specific variations in the obligate/facultative ratios as well as in the proportions of Firmicutes, Bacteroides, Actinobacteria and Proteobacteria communities are seen among these babies. This disparity even within this highly homogenous cohort manifests the magnitude of diverse patterns of gut microbiota configuration and hence underpins the importance of considering not only the gestational age, birth and feeding modes, and ethnic/ geographical background but also other potential outstanding factors when investigating the elements shaping the early microbiota development. In summary, the data demonstrate a quantitative bird’s-eye view of the ontogenesis of early-life gut microbiota in typically natural and healthy milieus and should be informative and facilitative for future studies exploring various aspects of the human gut microbiota.